Comment on "A hybrid multi-objective cultural algorithm for short-term environmental/economic hydrothermal scheduling" by Lu et al. [Energy Convers. Manage. 52 (2011) 2121–2134]. (15th July 2015) - Ahmadi, Abdollah; Nezhad, Ali Esmaeel; Heidari, Alireza; Agelidis, Vassilios G.
Abstract: This paper aims to discuss the short-term hydrothermal scheduling problem [Energy Convers. Manage. 52 (2011) 2121–2134], while a Hybrid Multi-Objective Cultural Algorithm (HMOCA) has been employed to solve the presented problem. This problem has been proposed in a multi-objective framework with fuel cost and emission of thermal units as two objective functions aimed to be minimized, simultaneously. However, there are some inaccuracies made by the authors in the mentioned reference, while presenting the solutions. In this regard, the results obtained for the water discharge rate of hydro units and accordingly, the optimal values derived for the power produced by such units are inaccurate and must be corrected for the optimal hydrothermal scheduling. Therefore, the present paper first highlights these inaccuracies and afterwards, epsilon-constraint technique and lexicographic optimization are used to propose the correct solutions.